THE IMPACT OF BRICK KILN OPERATION TO THE DEGRADATION OF TOPSOIL QUALITY OF AGRICULTURAL LAND - Md. Sirajul Islam; Shamim Al Mamun; Muliadi Muliadi; Sohel Rana; Tanmoy Roy Tusher; Shimul Roy (AGRIVITA, Journal of Agricultural Science, 2015)
Brick kiln is a big environmental issue for the agriculture of Bangladesh as it was observed that the agricultural production in the soil close to the brick kiln was lesser than the same soil far from brick kiln. The study was conducted to assess the impact of brick kiln operation to the degradation of topsoil quality at Singair of Kalihati upazila in Tangail, Bangladesh, during the period of July to December 2013. The Soil was collected from areas close to the brick fields and far from the brick fields at a depth of 0-15 cm. The Electrical Conductance (EC) was found almost double in the soil samples close to the brick field than the soil samples far from brick field. The organic mattter content in the soil sample close to the brickfield was significantly lower than that of the far soil sample. The mean values of total N, available P and S were also significantly lower in the soil samples close to the brick kiln, 0.05%, 12.4, and 8.36 ppm respectively in the close soils, while 0.06%, 24.6, and 11.7 ppm respectively in the far soil. There were no significant changes observed in the other elements.